Africa : Social and Economic Development Goals - A Progress Report - Mattimore, Angel (World Bank, Washington, DC, 2012)
During the 1998 Second Tokyo International Conference on African Development (TICAD II), a set of ambitious poverty reduction and human development goals were established for the Africa region, drawing on and reaffirming commitments made three years earlier at the First TICAD conference and at the United Nation (UN) Social Summit in Copenhagen. The Second TICAD Agenda for Action dealt with three broad areas: social development; economic development; and basic foundations for development (good governance, conflict prevention and post-conflict development). Nine time-bound social and economic development goals form a key part of the agenda: 1) Universal Primary Education (UPE) in Africa by 2015, with 80 percent completion by 2005; 2) halve the 1990 illiteracy rate by 2005, with an emphasis on improving female literacy rates; 3) gender equality in primary and secondary enrollments by 2005; 4) halve the 1990 maternal mortality rate by 2005, and by a further half by 2015; 5) reduce infant and child mortality rates to one-third of their 1990 levels by 2015; 6) universal access to reproductive health services by 2015; 7) halve the number of malnourished people by 2015; 8) safe water and sanitation for 80 percent of the population by 2005; and 9) reduce the number of women living in poverty by two-thirds by 2015.